MCSE exam 70-294 planning, implementing, and maintaining a Windows server 2003 Active Directory infrastructure : study guide & DVD training system - Cross, Michael, 1965- (Rockland, Mass. : Syngress Pub., 2003)
Syngress Study Guides guarantee comprehensive coverage of all exam objectives. There are no longer any short cuts or gimmicks that allow candidates to pass Microsoft's new, more rigorous exams. The days of cramming to become a "paper MCSE" are over; candidates must have a full grasp of all core concepts and plenty of hands-on experience to become certified. This book provides complete coverage of Microsoft Exam 70-277 and features one-of-a-kind integration of text, DVD-quality instructor-led training, and Web-based exam simulation and remediation, this study guide & DVD training system gives students 100% coverage of official Microsoft exam objectives plus realistic test prep. The System package consists of: 1) STUDY GUIDE. 800 pages of coverage explicitly organized in the identical structure of Microsoft's exam objectives. Sections are designed to "standalone", allowing readers to focus on those areas in which they are weakest and skim topics they may have already mastered. 2) DVD: A full hour of instructor-led training, complete with on-screen configurations and networking schematics, demystifying the toughest exam topics. 3) ONLINE PRACTICE EXAMS AND E-BOOK. Most exam candidates indicate that PRACTICE EXAMS are their single most valuable exam prep tool. Buyers of our Study Guides have immediate access to our exam simulations located at WWW.SYNGRESS.COM/SOLUTIONS. Syngress practice exams are highly regarded for rigor or the questions, the extensive explanation of the right AND wrong answers, and the direct hyperlinks from the exams to appropriate sections in the e-book for remediation. Readers will be fully prepared to pass the exam based on our 100% Certified guarantee. Readers may save thousands of dollars required to purchase alternative methods of exam preparation. Because of its breadth of coverage, this book will serve as a post-certification reference for IT professionals.
Includes index.
Keywords: Microsoft Windows server; Electronic data processing personnel -- Certification; Microsoft software -- Examinations -- Study guides; Directory services (Computer network technology) -- Examinations -- Study guides; Electronic books; Study guides